Learning With and From Indigenous People: Navigating Transformative Pedagogy and Privilege in Teacher Education - Kearns, Laura-Lee (Alberta Journal of Educational Research, 2020)
This case study explores the impact of an English language Arts Secondary methods class that focused on learning with and from Indigenous people. By participating in a number of in-class activities, taking a field trip, and engaging in a critical service-learning project that helped decentre the learner/teacher relationship, many non-Indigenous pre-service teachers were able to transform their understandings. Quantitative and qualitative data illustrate that most pre-service teachers challenged stereotypes, deficit thinking, and expanded their awareness; however, a minority experienced some levels of cognitive dissonance as their own privileged worldviews were challenged. This study explores the hope and challenges of decolonizing education, and a continuing need to imagine otherwise. Key words: decolonization, pre-service teacher education, social justice, Indigenous curriculum, calls to action Cette étude de cas porte sur l’impact d’un cours d’anglais en méthodologie au secondaire visant l’apprentissage avec, et de, personnes autochtones. Plusieurs enseignants non-autochtones en formation ont pu transformer leur compréhension en participant à des activités en classe, à une sortie éducative et à un projet d’apprentissage par le service qui a aidé à décentrer le rapport apprenant/enseignant. Les données quantitatives et qualitatives indiquent que la plupart des enseignants en formation ont fait abstraction des stéréotypes, ont surmonté des lacunes de raisonnement et ont amélioré leurs connaissances; toutefois, une minorité d’entre eux ont ressenti une certaine dissonance cognitive face à la remise en question de leurs propres visions du monde privilégiées. Cette étude explore l’espoir et les défis face à la décolonisation de l’éducation et du besoin permanent d’imaginer le monde autrement. Mots clés : décolonisation, formation préalable des enseignants, justice sociale, curriculum autochtone, Appels à l’action